This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
∫ 0 2 ln ϕ ln ( 2 sinh ( 2 x ) ) d x = ∫ 0 2 ln ϕ ln ( e x / 2 e x − 1 ) d x = ∫ 0 2 ln ϕ ln ( e x − 1 ) d x − ∫ 0 2 ln ϕ 2 x d x
Now let u = e x . Then we can rewrite the integral: = ∫ 1 ϕ 2 u ln ( u − 1 ) d u − ln 2 ( ϕ ) Let's rewrite it once again using integration by parts: = − ln 2 ( ϕ ) + ln ( u ) ln ( u − 1 ) ∣ 1 ϕ 2 − ∫ 1 ϕ 2 u − 1 ln ( u ) d u Make the substitution y = u 1 : = ln 2 ( ϕ ) + ∫ 1 1 / ϕ 2 y 2 − y ln ( y ) d y = ln 2 ( ϕ ) + ∫ 1 1 / ϕ 2 y − 1 ln ( y ) d y − ∫ 1 1 / ϕ 2 y ln ( y ) d y = ln 2 ( ϕ ) − Li 2 ( 1 − y ) ∣ 1 1 / ϕ 2 − 2 ln 2 ( y ) ∣ 1 1 / ϕ 2 = − ln 2 ( ϕ ) − Li 2 ( ϕ 1 )
To find the value of this expression, I am going to use three lemmas involving the dilogarithm:
( 1 ) ( 2 ) ( 3 ) Li 2 ( z 2 ) = 2 Li 2 ( z ) + 2 Li 2 ( − z ) Li 2 ( z ) + Li 2 ( 1 − z ) = 6 π 2 − ln ( z ) ln ( 1 − z ) Li 2 ( z ) + Li 2 ( z − 1 z ) = − 2 1 ln 2 ( 1 − z )
These can all be proved easily by differentiating, so I won't waste time with that here.
If we substitute z = ϕ 1 into the first equation and z = ϕ 2 1 into the others, we get the following system of equations:
( 1 ) ( 2 ) ( 3 ) Li 2 ( ϕ 2 1 ) = 2 Li 2 ( ϕ 1 ) + 2 Li 2 ( ϕ − 1 ) Li 2 ( ϕ 2 1 ) + Li 2 ( ϕ 1 ) = 6 π 2 − 2 ln 2 ( ϕ ) Li 2 ( ϕ 2 1 ) + Li 2 ( ϕ − 1 ) = − 2 1 ln 2 ( ϕ )
From this system we get Li 2 ( ϕ 1 ) = 1 0 π 2 − ln 2 ( ϕ ) . Therefore the value of the integral is − 1 0 π 2 .